Ankylosing spinal hyperostosis or forestier disease: difficulty in diagnosing or lack of knowledge? - E. N. Skryabina; N. A. Magdeeva; Y. M. Korneva (SINAPS LLC, 2020)
The article demonstrates a clinical case of a disease that occurs mainly in older age groups - ankylosing spinal hyperostosis (AHP) or Forestier disease. The rarity and lack of knowledge of AHP and the associated lack of alertness in relation to this disease makes its diagnostic a difficult task. The disease is more common in older people, which requires differential diagnosis with degenerative changes of the vertebrae. AHP is a low-symptom disease. Clinical symptoms are determined not so much by hyperostosis of the ligaments and tendons by themselves, but by the development of reactive inflammation of these structures during the process of ossification, overloading of still moving segments of the spine adjacent to ankylosed vertebrae. Of particular importance for this disease is the defeat of the anterior longitudinal ligament, the continuity of its ossification for at least four vertebrae (in contrast to trauma, tumors). Important is absence or low severity of ankylosis of the arched joints, sacroiliitis, characteristic of ankylosing spondylitis. The absence or weak severity of degenerative changes in the intervertebral discs detected in osteochondrosis matters. The presence of laboratory and clinical signs of inflammation, damage to other organs and systems is not typical to this pathology. At present time we have no treatment standards for AHP, which also makes the choice of patient management tactics complicated.The insufficient amount of information about this disease makes wider coverage of the pathology necessary in order to improve diagnostic skills, prescribing timely and complete treatment.